Distribution of Selenium in Corn and Its Relationship With Soil Selenium in Yutangba Mini—Landscape - 朱建明 毛大均 等 (Acta geochimica, 2000)
Within the range of 0.01 km^2 mini-landscape in Yutangba,Enshi,Hubei Province,the content of Se in corn is very high,The average Se contents in root,stem,leaf and seed of corn were estimated to be 4.36±3.27mg.kg,3.08±2.24mg/kg,9.74±7.62mg/kg,and 8.07±5.02mg/kg,respectively.The research results show that there is a significantly poistive correlation between corn selenium and soil selenium,and thus according to the distribtuion of Se in corn.Three subregions can be divided in Yutangba,The content of selenium in corn is controlled by that of soil.A little variation in selenium content in soil will lead to a considerable corresponding variation in corn.So it is deduced that the organs that contain relatively high Se in plants may be used as a sensitive selenium indicator of Se levels in the environment.